Analisis Permasalahan Msdm Pada Sistem Promosi, Demosi Dan Mutasi Jabatan Di Pt Bank Rakyat Indonesia (PERSERO) Tbk Cabang Mamuju - Nur Annisa; Agus Halim (CV. SINAR HOWUHOWU, 2026)
important role in helping organizations achieve their goals, especially in the banking sector which requires good performance and service. One of the key policies in HRM is the system of promotion, demotion, and job transfer.The aim is to place employees according to their abilities, work performance, and organizational needs. This study aims to analyze HRM issues related to the promotion, demotion, and job transfer system at PT Bank Rakyat Indonesia (Persero) Tbk Mamuju Branch. This research uses a qualitative method with a descriptive approach, namely through a literature study in the form of books, scientific journals, and other relevant sources. The results of the analysis show several problems, including subjective perceptions in the promotion process, a lack of transparency and clear indicators in the implementation of demotions, and job transfers that do not take into account the abilities of employees appropriately. These issues have a negative impact on employee morale and work performance. Therefore, it is necessary to implement a more objective, transparent, and competency-based HRM system to improve the smooth management of human resources in banking.